Modeling and analysis of multi-party non-repudiation protocols with extended-CSP approach - Zhi-geng HAN; Geng CHEN; Jun-zhou LUO (Tongxin xuebao)
Follow with the methodology of reverse engineering,an exploratory modeling and analysis of security of the typical Kremer-Markowitch multi-party non-repudiation protocol were carried out with a novel method named extended-CSP approach which had been proposed for two-party non-repudiation protocol in preliminary work.With the analysis,the inherent fact that this protocol statisfies not timeliness but non-repudiality and fairness was found successfully.The result of the analysis indicates that,as applying to two-party non-repudiation protocols,the extended-CSP approach can also be a new method for security verification of multi-repudiation protocols.